Evidential adverbials in Lithuanian: a corpus-based study - Ruskan, Anna (Kalbotyra, 2015)
The present study examines the functional distribution of the adverbials akivaizdžiai ‘evidently’, aiškiai ‘clearly’, ryškiai ‘visibly/clearly’, tariamai ‘allegedly/supposedly’ and aišku ‘clearly/of course’ in Lithuanian fiction and academic discourse. The aim of the study is to identify the evidential and/or pragmatic functions of perception and communication-based adverbials which can be traced synchronically to different syntactic environment (a predication manner adverbial and a CTP clause). The paper examines the frequency of these adverbials, their position, scope, functions, co-occurrence with argumentative markers, word class (adverb or non-agreeing adjective) and the type of discourse they occur in. The research is conducted by applying a corpus-based methodology and the data are obtained from the Corpus of the Contemporary Lithuanian Language, namely from the subcorpus of fiction, and the Corpus of Academic Lithuanian. The perception-based adverbials akivaizdžiai ‘evidently’, aiškiai ‘clearly’, ryškiai ‘clearly/visibly’ and aišku ‘clearly/of course’ denote inferences drawn from perceptual and conceptual evidence and contribute to persuasive authorial argumentation, while the communication-based adverbial tariamai ‘allegedly/supposedly’ functions as a hearsay marker. The latter may also be used as an epistemic marker which refers to unreal or imagined situations. In contexts of common knowledge, the adverbial aišku ‘clearly/of course’ acquires interactional and textual functions and thus reveals traces of pragmaticalisation. In academic discourse, it signals interaction with the addressee and links units of discourse, while in fiction it functions as a speech act modifier in a variety of emotive contexts. The pragmaticalisation of aišku ‘clearly/of course’ is also marked by its high frequency, positional mobility (initial, medial, final) and scopal variability (clausal, phrasal). Alongside its discrete evidential and pragmatic functions, the adverbial aišku ‘clearly/of course’ displays the merger of the two functions. The adverbials akivaizdžiai ‘evidently’, aiškiai ‘clearly’, ryškiai ‘visibly/clearly’ and tariamai ‘allegedly/supposedly’ do not acquire a pragmatic function, which is indicated by their frequency and position. The results of the present study corroborate the findings of previous studies that common sources of evidential adverbials and pragmatic markers in Lithuanian are verb-based, adjective-based and noun-based CTP clauses.
Keywords: evidential adverbial; inference; hearsay; pragmatic marker; fiction; academic discourse